Paciente de sexo femenino de 42 años de edad con cuadro clínico de VIH - Zambrano Macias, Dagmar Liseth (2018)
This case study was carried out in order that people who still have it as a taboo see that it is not a disease that they must be afraid of because thanks to the technology that has advanced a lot in all these years since that appeared There are many medications ready to take effect in every person who is infected by this disease. It seemed to me a very nice case which I was also afraid of, but when I knew that there were medications to diminish the way they multiply and make the person raise their defenses during the time of treatment they can live a stable life like any other. Another person must remember that for God we are all equal before his eyes no one in this life is perfect the only one is the nobody else.